Implementation of Guidance and Supervision Functions for Land Deed Officials at the Tangerang District Land Office - Emilia, Emilia; Atalim, Stanislaus (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
In the Tangerang Regency area, the task of fostering and supervising the Land Deed Official is carried out by the Tangerang Regency Land Office with the hope that the implementation of the Land Deed Official's professional duties can be achieved optimally and minimize violations of the law in carrying out their duties. For this reason, it is necessary to know the extent to which the implementation of the guidance and supervision function of the Land Deed Officials in Tangerang Regency is carried out. This research was using normative juridical research, library law research supported by interviews, with the nature of analytical descriptive research which is expected to obtain a systematic and detailed description of the problems to be studied, then it can be concluded in this study that the guidance and supervision of Land Deed Officials in Tangerang Regency has not been implemented properly and optimally. This is due to the factor that the area in Tangerang Regency is very large and has more than 400 Land Deed Officials which is not comparable to the guidance and supervision resources owned by the Tangerang Regency Land Office personnel. Another factor that becomes an obstacle is the rules that tend to be weak, do not provide strict sanctions, such as the existence of a Land Deed Official who does not submit reports on the making of his deed on a regular basis. Suggestions and recommendations for this research are in the form of perfecting rules and provisions for stricter sanctions as well as scheduling systematic guidance and supervision by the Tangerang District Land Office.